Effects of treatment beyond the treated: a general equilibrium impact evaluation of Lesotho's cash grants program. (28th January 2015) - Filipski, Mateusz J.; Taylor, J. Edward; Thome, Karen E.; Davis, Benjamin
Abstract Africa's social cash transfer programs target the most resource‐constrained households, unlikely to expand supply in response to transfer‐induced demand. We propose a local economy‐wide impact evaluation model and use it to evaluate local spillovers from Lesotho's Child Grants Program. We report Monte‐Carlo confidence bounds around impact‐simulation results. We find significant spillovers to nonrecipient households and significant real income multipliers, although the latter are dampened if factor supply constraints generate excessive inflationary pressures. Our findings raise questions about how to measure the impacts of cash transfers. Evaluations focusing only on eligible households are likely to significantly understate program impacts.